LDAP authentication for IBM DS8000 systems - Dufrasne, Bertrand (IBM redpaper., 2018)
The IBM® DS8000® series includes the option to replace the locally based user ID and password authentication with a centralized directory-based approach. This IBM Redpaper"!publication helps DS8000 storage administrators understand the concepts and benefits of a centralized directory. It provides the information that is required for implementing a DS8000 authentication mechanism that is based on the Lightweight Directory Access Protocol (LDAP). Starting with DS8000 Release 7.5, directory-based authentication relies on IBM Copy Services Manager (CSM) that provides the interface (the CSM LDAP client) between the DS8000 and external LDAP servers